2008
DOI: 10.1002/pc.20735
|View full text |Cite
|
Sign up to set email alerts
|

Conductive polyaniline/polyacrylonitrile composite fibers: Effect of synthesis parameters on polyaniline content and electrical surface resistivity

Abstract: Conductivepolyaniline/polyacrylonitrile (PAn/PAN) composite fibers were prepared by keeping PAN fibers in various solutions containing aniline and then by polymerization of aniline sorbed by fibers with potassium dichromate as an oxidant. In examined polymerization media, aqueous HCl gave composite fibers with the highest PAn amount and these fibers also had the lowest electrical surface resistivity. It was found that, as PAn content of PAn/PAN composite fibers increased, its density also increased and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Better mechanical properties, but lower conductance, usually is obtained in composite fibers. Toptaş et al obtained composite PAN/PANI fibers in a different method that was presented in this paper, but mechanical and electrical properties are comparable [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Better mechanical properties, but lower conductance, usually is obtained in composite fibers. Toptaş et al obtained composite PAN/PANI fibers in a different method that was presented in this paper, but mechanical and electrical properties are comparable [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, fibers from the PAN/PANI composition were made by electrospinning, where an increase in electrical conductivity towards polyacrylonitrile was observed [ 13 ]. Toptas et al obtained conductive polyaniline/polyacrylonitrile composite fibers by sorption of aniline and polyacrylonitrile fiber [ 14 ]. These fibers had satisfactory electrical conductivities, mechanical strengths, and resistances for laundering.…”
Section: Introductionmentioning
confidence: 99%
“…In the preparation of these composites, in situ chemical oxidative polymerization is one of the most preferred methods due to being relatively facile and one step, requiring relatively economic devices and enabling homogenous polymer deposition onto textile material. Numerous studies have been reported for the preparation of these composites with chemical oxidative polymerization using various oxidants . Among them, the polymerizations initiated by AgNO 3 oxidant have been promising because of providing the deposition of metallic Ag particles in addition to conductive polymer coating through the oxidative reaction between monomer and AgNO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, conducting polymers have widely been investigated due to their increasing number of applications in transistors, rechargeable batteries, chemical sensors, diodes, microelectronics etc. [1–10] Polyaniline is one of the most studied conducting polymers because of its low cost, excellent environmental stability, high electronic conductivity, and relative ease of the synthesis. Polyaniline has four different states (leucoemeraldine base, emeraldine base, pernigraniline base, and emeraldine salt).…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline has four different states (leucoemeraldine base, emeraldine base, pernigraniline base, and emeraldine salt). Among the above forms of PANI, only the emeraldine salt form is conductive and it can be synthesized by a simple electrochemical or chemical oxidation of aniline in an acidic medium [1, 2, 5–21].…”
Section: Introductionmentioning
confidence: 99%